Student Psychological Well-Being Plays Dual Roles During the Pandemic Covid-19 - Rina Suryani (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
The psychological well-being experienced by students, disrupting normal daily life is a condition where they experience psychological problems that cannot function positively and well. In this study, it explains how the psychological well-being experienced by students in the face of the Covid-19 pandemic. qualitative descriptive. Participants involved in this study are students who study while working to make ends meet. This is because Covid-19 has a psychological impact on participants' psychological conditions. The conditions experienced are anxiety, fear and stress related to the transmission of the Covid-19 pandemic. this and conditions that should not leave thehouse.